The Relationship Between Peer Conformity and Bullying Behavior in the Work Area of Soropia Community Health Center - Wa Ode Nova Noviyanti; Cece Indriani; Nazaruddin Nazaruddin; Nurdin Nurdin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Bullying is a deliberate activity aimed at hurting and intimidating through unequal power dynamics, with the potential to cause trauma and instil fear. This phenomenon occurs in various contexts, such as schools, workplaces, or online, and encompasses physical, verbal, social, and psychological violence. Its impacts are highly detrimental, including psychological trauma, decreased academic performance, depression, anxiety, and even suicide risk for victims, as well as potential future behavioural problems for perpetrators. Environments that tolerate bullying can create unhealthy and fear-filled atmospheres. This study aims to examine the relationship between peer conformity and bullying behavior in the working area of the Soropia Community Health Center. Methods: This research used a quantitative study design with a cross-sectional approach. The study population consisted of 52 respondents, with a sample of 46 respondents selected using consecutive sampling techniques. The instrument utilized was a questionnaire. Results: The Fisher Exact Test showed a significant relationship, with a ? value of 0.000 < 0.05 and X² calculated = 40.310 > X² table = 3.841. Therefore, H? was rejected, and H? was accepted, indicating a positive relationship between peer conformity and bullying behavior in the working area of the Soropia Community Health Center. Conclusion: Relevant stakeholders are encouraged to collaborate, including individuals, families, educational institutions, and the broader community, in efforts to prevent and address bullying, thereby creating a safe and supportive environment for all. The findings of this study are expected to provide useful information for adolescents to avoid bullying behavior and maintain harmony.